2008
DOI: 10.1371/journal.pone.0003064
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Role of Host Genetics in Controlling the Composition of Gut Microbiota

Abstract: BackgroundThe human gastrointestinal tract is inhabited by a very diverse symbiotic microbiota, the composition of which depends on host genetics and the environment. Several studies suggested that the host genetics may influence the composition of gut microbiota but no genes involved in host control were proposed. We investigated the effects of the wild type and mutated alleles of the gene, which encodes the protein called pyrin, one of the regulators of innate immunity, on the composition of gut commensal ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
202
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(214 citation statements)
references
References 94 publications
7
202
1
4
Order By: Relevance
“…Some of these studies address fine genetic scales, such as monozygotic, human twins (Turnbaugh et al, 2009) and wellcharacterized host mutations (Vaahtovuo et al, 2005;Khachatryan et al, 2008). Others have addressed the effects of host genetics on the gut microbiome on a larger scale with studies of species of primates (Ley et al, 2008a;Ochman et al, 2010) and various animals in captivity or the wild (Ley et al, 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies address fine genetic scales, such as monozygotic, human twins (Turnbaugh et al, 2009) and wellcharacterized host mutations (Vaahtovuo et al, 2005;Khachatryan et al, 2008). Others have addressed the effects of host genetics on the gut microbiome on a larger scale with studies of species of primates (Ley et al, 2008a;Ochman et al, 2010) and various animals in captivity or the wild (Ley et al, 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…These measures have suggested that community assemblages correlate with salinity , diet (Ley et al, 2008), pH (Jones et al, 2009;Lauber et al, 2009), and host genotype (Khachatryan et al, 2008). We used a similar approach to explore the factors affecting bacterial community assembly in prairie dog fleas sampled across space and time.…”
Section: Bacterial Diversity Within Individual Fleasmentioning
confidence: 99%
“…These diseases are well understood to be multifactorial, with both environmental and genetic components (11)(12)(13), and the contribution of the gut microbiota is currently viewed as an environmental factor (14). Although a number of studies have suggested that composition of the gut microbiota may be subject to host genetic forces, existing evidence is conflicting and confounded by the genetic diversity of vertebrate (especially human) populations and strong environmental effects (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%